1993
DOI: 10.1111/j.2044-8341.1993.tb01762.x
|View full text |Cite
|
Sign up to set email alerts
|

A three‐month follow‐up of psychological morbidity after early miscarriage

Abstract: The loss of a pregnancy in the first trimester is a common event and recent research has identified high levels of psychological distress amongst women who have miscarried. We believe this study is the first to examine the phenomenon from a longitudinal perspective using standardized measures. A sample of 65 women was rated for anxiety and depression using the Hospital Anxiety and Depression Scale at intervals of one, six and 12 weeks following early miscarriage. The results indicate that a large proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(36 citation statements)
references
References 7 publications
4
31
1
Order By: Relevance
“…This is also reflected in the perception of women with regard to the health care system (32). Other women have described gaps in the information provided by the health care system and the lack of empathy for those who have experienced miscarriage (18,28). The typical reaction among health professionals is to think of a miscarriage occurring in the first trimester as a rather common incident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also reflected in the perception of women with regard to the health care system (32). Other women have described gaps in the information provided by the health care system and the lack of empathy for those who have experienced miscarriage (18,28). The typical reaction among health professionals is to think of a miscarriage occurring in the first trimester as a rather common incident.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of depression in post-miscarriage are found in between 45%–50% of the women during the first few weeks after the loss (15,16). Anxiety has been measured and identified after miscarriage (17,18), and even post-traumatic stress has been identified (19). …”
Section: Introductionmentioning
confidence: 99%
“…Approximately 14% and 0.5% of all clinically-recognized pregnancies in the United States result in miscarriage and stillbirth, respectively (Saraiya, Berg, Shulman, Green, & Atrash, 1999). Since the 1980s, research has shown that women (and to a lesser extent, their partners) experience a variety of psychological distress outcomes following pregnancy loss, including grief, anxiety, depression, and guilt (Friedman & Gath, 1989; Greil, 1991; Leppert & Pahlka, 1984; Prettyman, Cordle, & Cook, 1993), and that these outcomes are often sustained over time (Lee, Slade, & Lygo, 1996; Neugebauer et al, 1997; Robinson, Stritzinger, Stewart, & Ralevski, 1994). These issues associated with pregnancy loss are far-reaching, and result in extensive stress and even marital conflict (Goodwin, 2002).…”
Section: Pregnancy Lossmentioning
confidence: 99%
“…Previous studies have found variables affecting distress following early pregnancy loss (EPL) such as gestational age (Toedter, Lasker, & Alhadeff, 1988), planned versus unplanned pregnancy (Tharpar & Tharpar, 1992), other “loss” experiences (Garel et al, 1992), and pre-loss psychiatric symptoms (Janssen, Cuisinier, de Graauw, & Hoogduin, 1997; Prettyman et al, 1993). Childlessness has also been reported to be a specific risk factor associated with increased levels of grief among women following pregnancy loss (Janssen et al, 1997).…”
Section: Pregnancy Lossmentioning
confidence: 99%
“…[3][4][5] Such symptoms decline over time, to levels equivalent to the non-pregnant population at 1 year. 6 In general, anxiety is more marked than depression.…”
Section: Introductionmentioning
confidence: 99%